Dental hygienist attendance and its covariates in an ageing Swedish cohort. (30th October 2017) - Åstrøm, Anne N.; Ekbäck, Gunnar; Ordell, Sven; Lie, Stein A.; Gulcan, Ferda
Abstract : Delegation of tasks between professional groups is important to make health‐care services accessible and effective for ageing people. Focussing on a Swedish 1942 birth cohort and guided by Andersen's Behavioral Model, this study assessed dental hygienist attendance from age 50 to age 70 and identified covariates at the population‐averaged and person‐specific levels. In 1992, a census of 50‐yr‐old subjects was invited to participate in a questionnaire survey. Of the 6, 346 respondents, 3, 585 completed follow‐ups in 1997, 2002, 2007, and 2012. Multiple logistic regression analysis was conducted using a marginal model and a random intercept model. Cochran's Q test revealed that significantly more respondents confirmed dental hygienist attendance in 2012 than in 1992 (57.2% in 2012 vs. 26.0% in 1992). Population‐averaged ORs for dental hygienist attendance across time were 3.5 at age 70 yr compared with age 50 yr (baseline); 2.0 if being a regular rather than an irregular dental attendee; and 0.7 if being of non‐native origin compared with native origin. The corresponding person‐specific ORs were 8.9, 3.2, and 0.5. Consistent with Andersen's Behavioral Model, predisposing, enabling, and need‐related factors were associated with dental hygienist attendance at population‐averaged and person‐specific levels. This has implications for promoting dental hygienist attendance among ageing people.